1999
DOI: 10.1046/j.1432-1327.1999.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity labelling with MgATP analogues reveals coexisting Na+ and K+ forms of the α‐subunits of Na+/K+‐ATPase

Abstract: To test the hypothesis that Na + /K + -ATPase works as an (ab) 2 -diprotomer with interacting catalytic a-subunits, tryptic digestion of pig kidney enzyme, that had been inactivated with substitution-inert MgATP complex analogues, was performed. This led to the demonstration of coexisting C-terminal Na + -like 80-kDa as well as K + -like 60-kDa peptides and N-terminal 40-kDa peptides of the a-subunit. To localize the ATP binding sites on tryptic peptides, studies with radioactive MgATP complex analogues were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
11
0
4
Order By: Relevance
“…Simple arithmetic calculations thus give an ASPD:NAKα3 ratio ranging from 1:1-1:3. However, because past studies have shown that the NAK pump exists predominantly as (NAKα3) 2 :(NAKβ1) 2 heterotetramer in membranes (35,36) and ASPD appeared to bind almost all NAKα3-containing NAK pumps in membranes (Fig. 3E), we infer, using Occam's razor (37), that the most likely ratio is 1:2 (i.e., 1:1 binding of ASPD with NAKα3 dimer).…”
Section: Aspd Bind To Nakα3mentioning
confidence: 74%
“…Simple arithmetic calculations thus give an ASPD:NAKα3 ratio ranging from 1:1-1:3. However, because past studies have shown that the NAK pump exists predominantly as (NAKα3) 2 :(NAKβ1) 2 heterotetramer in membranes (35,36) and ASPD appeared to bind almost all NAKα3-containing NAK pumps in membranes (Fig. 3E), we infer, using Occam's razor (37), that the most likely ratio is 1:2 (i.e., 1:1 binding of ASPD with NAKα3 dimer).…”
Section: Aspd Bind To Nakα3mentioning
confidence: 74%
“…The specific antibody (rSGLT1-Ab) was affinity purified from the immune serum via the antigenic peptide-coupled support (9). The use of a polyclonal anti-Na-K-ATPase ␣-subunit antibody has been described (2,6). A monoclonal antibody against ␣-actin was purchased commercially (Chemicon, Temecula, CA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the αβ form of the Na,K-ATPase is capable of both ATP hydrolysis and active ion transport (Ward and Cavieres 1993, Martin et al 2000Miles et al 2011). However, accumulating evidence suggests that the enzyme normally self associates as (αβ) 2 dimers (Santos et al 2002(Santos et al , 2006bThoenges and Schoner 1997;Antolovic et al 1999;Costa et al 2003;Santos and Ciancaglini 2003) or as (αβ) 4 tetramers (Mahaney et al 1990;Donnet et al 2001;Taniguchi et al 2001).…”
Section: Applications For the Study Of Lipid-protein Interactionsmentioning
confidence: 99%